Physiological and sanitary quality of maize seeds treated with cambuci [Campomanesia phaea (O. Berg) landrum] extract (Bioagro, 2025)
The control of phytopathogens using plant extracts has been identified as an alternative to organic agriculture, which excludes the use of toxic and synthetic substances. The present study aimed to evaluate the sanitary and physiological potential of organic maize seeds treated with cambuci extract (Campomanesia phaea). Two plant extracts were tested, obtained from different tissues of the C. phaea species (fruit peel and leaf, fresh and dry), in the following concentrations: 0, 25, 50, 75 and 1000 %. The content of total phenolic compounds was found to be higher in the leaf extract (at 100 % concentration was 409.7 % higher in the leaf compared to the peel), particularly when prepared with fresh tissue. The dry peel extract was observed to increase the percentage and speed index of maize seed germination, without, affecting the biometric variables of the seedlings. Extracts from fresh cambuci leaves demonstrated a reduction in the percentage of fungi of the genus Fusarium. However, at a concentration of 50%, a phytotoxic effect of this extract on maize seeds was observed, which resulted in a reduction in germination and the length and dry mass of the seedlings. Our findings suggest that cambuci extract represents a promising strategy in the ecologically correct treatment of organic maize seeds, provided if it is applied at the appropriate concentration.
Keywords: Natural treatment; plant extracts; Zea mays